Detection of porcine reproductive and respiratory syndrome virus (PRRSV) and influenza A virus (IAV) in oral fluid of pigs. (December 2016) - Biernacka, Kinga; Karbowiak, Paweł; Wróbel, Paweł; Charęza, Tomasz; Czopowicz, Michał; Balka, Gyula; Goodell, Christa; Rauh, Rolf; Stadejek, Tomasz
Abstract: Recently oral fluid has become a novel sample type for pathogen nucleic acid and antibody detection, as it is easy to obtain with non-invasive procedures. The objective of the study was to analyze porcine reproductive and respiratory syndrome virus (PRRSV) and influenza A virus (IAV) circulation in growing pigs from three Polish production farms, using Real Time PCR and ELISA testing of oral fluid and serum. Oral fluids were collected every 2 weeks, in the same 3–4 pens of pigs aged between 5 and 17 weeks. Additionally, blood samples were collected every 4 weeks from 4 pigs corresponding to the same pens as oral fluid and tested for the presence of PRRSV nucleic acid (pooled by 4) and antibodies. In farm A no PRRSV circulation was detected and only maternal antibodies were present. In farm B and farm C antibodies to PRRSV in serum and oral fluid were detected in most samples. In farm B PRRSV Type 1 was detected in 80.9% of oral fluid samples and in 58.3% of serum pools, and in farm C in 92.8% of oral fluid samples and 75% serum pools. Striking differences were observed between different pens in PRRSV detection patterns. In farms B and C ORF5 sequence analysis showed the presence of wild type strains which were about 84–85% identical to the modified live vaccine used. In all three farms two waves of IAV shedding with oral fluid were detected, in weaners and fatteners. Highlights: Oral fluid can substitute serum for PRRSV surveillance and monitoring by ELISA and PCR. Striking differences were observed between different pens in PRRSV detection patterns. Oral fluid is a useful specimen for detection of endemic influenza in pigs. In all farms two waves of IAV shedding were detected, in the same groups of pigs.